VACCINATION CRISIS AS AN ENVIRONMENTAL THREAT TO PUBLIC HEALTH. AN ANALYSIS OF THE RESURGENCE OF DIPHTHERIA, PERTUSSIS AND MEASLES IN POLAND - Emilia Biczak; Oliwia Biegańska; Grzegorz Przywara; Hanna Barska-Kobylińska; Martyna Byrska; Maja Weimann; Marta Janura (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose of the Study: Protective vaccinations represent one of the greatest achievements in medicine. They have led to the elimination or reduction of many life-threatening infectious diseases. However, their success has also led to diminished awareness of the real threat posed by diseases, causing their resurgence in Poland and worldwide in recent years. This paper aims to analyze the current epidemiological situation of diphtheria, pertussis, and measles in Poland based on data concerning case numbers and the vaccination status of the population between 2010 and 2024.Current state of Knowledge: Analysis of National Institute of Public Health data has revealed a systematic decline in the percentage of individuals vaccinated against all three diseases, often falling below the herd immunity threshold. This resulted in a significant increase in the measles cases in 2019 and an alarming surge in pertussis cases in the 2024- 2025. After years of absence, there have also been isolated cases of diphtheria. Data indicate insufficient adult immunity, low booster uptake, and persistent vaccine-related myths.Conclusions: These findings clearly indicate that diphtheria, pertussis, and measles can pose a real threat to public health in Poland that can be directly linked to the decline in vaccination coverage. Urgent measures are needed, including improving coverage, promoting booster vaccinations in adults, education, and addressing vaccine hesitancy. Herd immunity remains essential for protecting public health and is a shared public responsibility.